Extraction and Effect of Saponin Extracted From Peel Of Musa acuminata Towards Sƒ9 Cells - Afrina, Zainal (2017)
Saponins are phytochemicals found in many plants. Their structural diversity make them to have various biological activities. Saponin is produced in various parts of plants such as fruits and fruit peels. Since saponin comes from the fruit waste as this source is more economical and it can be converted into a useful bioproduct. One of the properties of saponin currently being studied is the insecticidal properties. The aims of this research were to extract saponin from the peel of banana Musa acuminate by using three different sample preparation methods, namely dried, fresh and macerated peels, to determine the saponin content from the peel of banana, and the preliminary screen the insecticidal properties of saponin extracted on the growth of an insect cell line, Spodopetra frugiperda (Sf9). Fresh and macerated peels were prepared by blending and dried peels were oven-dried at 60°C before blended into powder. Both dried and fresh peels were exposed to solvent for 24 hours while the macerated peels was subjected to 72 hours. The extraction of saponin from the peels was done using two solvents namely, 50% (v/v) ethonal and 85% (w/v) hexane. All extracts were profiled at wavelength ranging from 300 nm to 700 nm. These profiles were compared with and absorbance profile containing 5 ɲg/mL of quercetin (Qu) which was used as flavonoid standard. Total saponin (TS) content was qualified by treating the extracts with vanillin and sulfuric acid, and the absorbance were recorded at 544 nm. the Sƒ9 cells in suspension were treated with fresh-ethanol crude peel extract at a volume-to-volume ratio 1:1 for 24 hours and the cell growth was measured its absorbance at 630 nm. From the profiling of crude peel extracts, dried extracts in ethanol in which these two extracts shared similar absorbance profile. In addition, hexane was able to extract saponin in fresh peel better than ethanol by giving higher absorbance profile. This observation of fresh peel extract was in contrast to the macerated peel extract. Based on the total saponin assay, dried peel extracts in ethanol. Total saponin contents in both fresh and macerated extracts were higher when hexane was used as the extraction solvent compared to ethanol. Fresh-hexane extract was found to contain more flavonoids compared to fresh-ethanol, macerated-ethanol and macerated-hexane extracts based on the comparison of peaks at 380 nm of quercetin absorbance profile. The percentages of growth inhibition Sƒ9 cells treated with fresh-ethanol extract and 50% (v/v) ethanol was 8.04% and 7.59% respectively. In conclusion dried peel extract in ethanol has higher saponin compared to both fresh and macerated extracts based on the absorbance profiling and tS assay. Hexane was suggested as the suitable solvent to extract saponin compared to ethanol. The inhibition of Sƒ9 cells’ growth with fresh-ethanol extract did not show any significant difference with the solvent used.